Reshaping economic geography overview (World development report, 2009)
Concern for these three intersecting billions often comes with the prescription that growth must be spatially balanced. This report has a different message: economic growth will be unbalanced. To try to spread it out is to discourage it--to fight prosperity, not poverty. But development can still be inclusive, even for people who start their lives distant from dense economic activity. For growth to be rapid and shared, governments must promote economic integration, the pivotal concept, as this report argues, in the policy debates on urbanization, territorial development, and regional integration. Instead, all three debates overemphasize place-based interventions. Reshaping Economic Geography reframes these debates to include all the instruments of integration--spatially blind institutions, spatially connective infrastructure, and spatially targeted interventions. By calibrating the blend of these instruments, today's developers can reshape their economic geography. If they do this well, their growth will still be unbalanced, but their development will be inclusive."